Sediment Trapping and Carbon Sequestration in Floodplains of the Lower Atchafalaya Basin, LA: Allochthonous Versus Autochthonous Carbon Sources. Issue 3 (28th March 2019) - Hupp, Cliff R.; Kroes, Daniel E.; Noe, Gregory B.; Schenk, Edward R.; Day, Richard H.
Abstract: Recent studies suggest that about 2 Pg of organic C is stored on floodplains worldwide. The present study indicates the Atchafalaya River, fifth largest river in the United States in terms of discharge, traps 30 mm/year of sediment on average within its floodplain, which is the highest average nonepisodic rate of fluvial deposition on the U.S. Coastal Plain. We installed sediment sampling stations at 23 sites, normally in transect, in the Atchafalaya Basin; these sites represent the range of hydrogeomorphic conditions on the floodplain based on hydrologic connectivity with the river main stem. The rate of sedimentation translates into about 12.5 Tg/year and includes 694 Mg/year of organic C. Highest sedimentation rates are associated with areas of high connectivity to channels and prograding deltaic processes. The δ 13 C content suggests that 35% of deposited C is derived from river‐suspended sediment compared to litterfall in the basin. Thus, much of the organic C sequestered is allochthonous material. However, isolated interior sites with limited connectivity to the channel may generate and sequester large amounts of autochthonous C. The substantial trapping of both autochthonous and allochthonous C (392 Mg/year) make this freshwater‐forested floodplain critical in storage of material before reaching the coastal delta and estuary. This C deposition rate (340 g C·m −2 ·yr −1 ) exceeds all other rates reported in recent Blue Carbon and Tidal Freshwater Forested Wetland studies. Atchafalaya C sequestration occurs in/near areas with tidal influence and like other coastal systems is an important site for trapping mineral and organic sediment and in global C cycling. Key Points: Sources of carbon (allochthonous vs. autochthonous) for floodplain sequestration were successfully estimated using carbon isotope analyses Carbon deposition rates in the Atchafalaya Basin exceed all accounts for Blue Carbon and Tidal Freshwater Forested Wetland ecosystems Atchafalaya C sequestration is an important coastal area in trapping organic sediment and should be used in models of global C cycling